Diagnostic Yield of Lateral Decubitus Digital Subtraction Myelogram Stratified by Brain MRI Findings. (2nd March 2021) - Kim, Dong Kun; Carr, Carrie M.; Benson, John C.; Diehn, Felix E.; Lehman, Vance T.; Liebo, Greta B.; Morris, Jonathan M.; Morris, P. Pearse; Verdoorn, Jared T.; Cutsforth-Gregory, Jeremy K.; Atkinson, John L. D.; Brinjikji, Waleed
Abstract : Objective: To assess the diagnostic yield of lateral decubitus digital subtraction myelography (LDDSM) and stratify LDDSM diagnostic yield by the Bern spontaneous intracranial hypotension (SIH) score of preprocedure brain MRI. Methods: This retrospective diagnostic study included consecutive adult patients investigated for SIH who underwent LDDSM. Patients without preprocedure brain and spine MRI and patients with extradural fluid collection on spine MRI (type 1 leak) were excluded. LDDSM images and brain MRIs were assessed by 2 independent blinded readers; a third reader adjudicated any discrepancies. Diagnostic yield of LDDSM was assessed, both overall and stratified by Bern SIH scoring. Results: Of the 62 patients included in this study, 33 (53.2%) had a CSF leak identified on LDDSM. Right-sided leaks were more common (70.6%), and the most commonly identified levels of leaks were at T6, T7, and T10. No leak was found in any of the 9 patients with Bern SIH score of 2 or less. Of the 11 patients with Bern SIH score of 3–4, 5 (45.5%) had a CSF leak identified; of the 42 patients with Bern SIH score of 5 or higher, 28 (66.7%) had a CSF leak identified. Conclusions: LDDSM has a high diagnostic yield for finding the exact location of spinal CSF leak, and the diagnostic yield increases with higher Bern SIH score. No leaks were found in patients with Bern SIH score of 2 or less, suggesting that foregoing invasive testing such as LDDSM in these patients may be appropriate unless accompanied by high clinical suspicion. Classification of Evidence: This study provides Class II evidence that for patients with suspected SIH, higher Bern SIH scores are associated with a greater likelihood of LDDSM-identified CSF leaks.